Humor-based online positive psychology interventions: A randomized placebo-controlled long-term trial. Issue 6 (1st November 2016) - Wellenzohn, Sara; Proyer, René T.; Ruch, Willibald
Abstract : While correlational evidence exists that humor is positively associated with well-being, only few studies addressed causality. We tested the effects of five humor-based activities on happiness and depression in a placebo-controlled, self-administered online positive psychology intervention study ( N  = 632 adults). All of the five one-week interventions enhanced happiness, three for up to six months (i.e. three funny things, applying humor, and counting funny things), whereas there were only short-term effects on depression (all were effective directly after the intervention). Additionally, we tested the moderating role of indicators of a person × intervention-fit and identified early changes in well-being and preference (liking of the intervention) as the most potent indicators for changes six months after the intervention. Overall, we were able to replicate existing work, but also extend knowledge in the field by testing newly developed interventions for the first time. Findings are discussed with respect to the current literature.